A Sociolinguistic Study of Deviant Orthographic Representation of Graduating Students' Names in a Nigerian University - Faleye, Oladunjoye J.; Adegoju, Adeyemi (Linguistik Online, 2013)
It is habitual for graduating students of the Obafemi Awolowo University, Ile-Ife, Nigeria, to roll out the drums the very day they finish writing their final examination. Characteristic of such a ritualistic exercise, among other things, are the brand names the students coin for themselves from their original names. This study focuses on the creative rewriting of the names on such an occasion and examines the linguistic habits exhibited therein. It analyses the phonological/graphematic features that mark the rewritng of the names and discusses the sociolinguistic implications for the phenomena of social identity construction and language contact situation. Data for the study was sourced mainly through participant-observation technique with a supplemment of an oral interview conducted for some of the subjects between year 2007 and 2009. The data was selected through a purposive random sampling technique which yielded fifty names that were considered representative of the respelling conventions. The paper employs mainly Hempenstall's (2003) Phonological Sensitivity Skills to analyse the linguistic practices in the reconfigured names and then applies Tajfel's and Turner's (1979) Social Identity Theory to explain how it is that people develop a sense of membership and belonging in particular groups. The article reveals that the deviant orthographic conventions are a major fallout of youth culture with great influence from computer-mediated communication. It also shows that their linguistic experimentation foray in the discourse greatly undermines the orthographic system of the indigenous language (Yoruba) and the cultural values embedded in the original names.